Estimating monetary policy rules for South Africa - Aron, J; Muellbauer, J (University of Oxford, 2001)
Published in: Aron, J. and J. Muellbauer. 2002. "Estimating Monetary Policy Rules for South Africa", in Norman Loayza and Klaus Schmidt-Hebbel (eds) "Monetary Policy: Rules and Transmission Mechanisms", Series on Central Banking, Analysis and Economic Policies, Volume 4, Central Bank of Chile, pages 427-475. ISBN # 956-7421-09-9.